Project Based Learning and the Students’ Enthusiasm in Writing - fitri Wulandari (Journal of English Education, Literature and Linguistics, 2018)
Writing is not only productive skill that involves communicating in the form of letter or symbol but also involve a mental and learning process. Thus, the role of enthusiasm in the process of writing is very important. The researchers found some phenomena that referred to the problem of students’ enthusiasm in writing class. Based on some findings of previous research, project based learning was able to improve the students’ writing ability because it has challenging activity to be applied in every step of writing process.This study set out to investigate the using of project based learning in writing class. Thirty one of third year students at English Education Department in the academic year of 2017-2018STKIP Muhammadiyah Pringsewu Lampung attended this study. The lecturer applied project based learning at her advanced writing class. The design of the study was collaborative action research. The research found that the implementation of project-based learning at the advance writing class improved the students’ enthusiasm in writing.